Polifonia na educação: a formação docente na contemporaneidade - Ferreira, Luís Vicente (2010)
This study falls within the area of Social Sciences, more specifically in Anthropology. Has as its theme the continuing education of educators, more specifically in the search for understanding of the possible contributions that the approaches to complex thinking, and the Transdisciplinarity could point to the construction of proposed Continuing Education of Teachers Training. The text is organized in a reading knowledge of the dialogue between the anthropology of complex systems. It is intended to perform a multidimensional reading, seeking knowledge from various fields and pieces to add a reading complex and interdisciplinary theoretical assumptions from the perspective of planetary citizenship of Edgar Morin, reflective teacher training of Donald Schon, construction of teacher identity Antonio Novoa and Isabel Alarcão, construction of ethics by Terezinha Rios, construction of educators in the XXI century, from Selma Garrido. Later, a critical analysis of the discourse of competence of Phillippe Perrenoud of Francisco Imbernon, in contrast to the discourse of autonomy and emancipation of Paulo Freire and Morin. From these and other authors is to build a reading on the construction of multidimensional being, emphasizing the role of inconclusive complex reflexive teaching, to a suggestion of building knowledge and practices tailored to the needs of this time of transition in the education paradigm. It is the need of contemporary changes in educational processes, so that they meet the requirements of humanization, the consolidation of an antropoethic and global identity. Objective is more specifically discuss the limits of a culture of teacher education rooted in a reductionist conception of human beings, to a limited understanding rationalist, scientistic, mechanistic and dualistic world, a multifaceted approach and present a possibility of direct programmatic continuing teacher training. A sample of the empirical study built up during a journey to educators in a coastal city of Sao Paulo, in the continuity of the other inner cities. The results indicate that there is the urgent need to rethink the training of educators as well as the emergence of continuing education in service from a more complex and humanistic vision